Reading strategies of average and weak ESL readers: a case study - Spykerman, Angeline (1988)
This study approaches reading from the psycholinguistic standpoint. Miscue analysis is used to investigate the reading strategies of a group of average and weak ESL readers from Sekolah Menengah Bangsar, Kuala Lumpur. The readers' miscues were analyzed in accordance with Yetta Goodman and Burke's Reading Miscue Inventory (1972). The research addresses itself to the question of how these readers utilized the language cues - graphophonic, syntactic and semantic - to help them make sense of the text. The findings shows that both groups of readers depended extensively on graphophonic cues and were less efficient in using syntactic and semantic cues. Qualitative analysis of the miscues show that when the readers did resort to the syntactic and semantic cues, the average readers produced better quality miscues. The applicability of miscue analysis as a research tool is indicated in the suggestions for further research. The pedagogical implications of the findings underscore the practical use of miscue analysis in the classroom.